Desenvolvimento e caracterização de microemulsões com óleo essencial Syzygium aromaticum dispersas em hidrogéis com ação larvicida contra o Aedes aegypti - Rezende, Brena Monaline de Menezes (2017)
Due to the negative aspects obtained by the discriminated use of chemical insecticides, essential oils appear as a natural alternative in the control of the Ae Aegypti mosquito. However, these oils present some limitations that can be overcome through the use of microemulsions (MEs) that increase the solubilization of the active principle and stability of the system. The combination of MEs with polymeric hydrogels can further preserve the structure in aqueous medium. Thus, the objective of this work was to develop and characterize MEs with essential oil of Syzygium aromaticum (OESA) dispersed in hydrogels based on poly (hydroxyethyl methacrylate), p (HEMA). OESA has as main component eugenol that has potential larvicidal effect against the mosquito Aedes aegypti. We sought a system that in aqueous media allows the active principle release, enabling a reduction in the proliferation of the mosquito vector. The ME preparation consisted from OESA, Tween 80 (surfactant) and water. The incorporation of an inorganic phase from methacryloxypropyltrimethoxysilane (MPTS) and ethylene glycol dimethacrylate crosslinking agent (EDGMA) influenced the final structure of the polymeric hydrogels favoring the formation of more rigid and crosslinked polymers, increasing the stability thermal, but decreasing the capacity of water uptake (swelling). The water uptake in the system influences the release kinetics in matrix systems. The composition of the hydrogels influenced the mortality rates of Ae. aegypti in the first 24 hrs, ranging from 11.6 to 66.6% depending on the combination of whether or not MPTS and EDGMA were present in the sample. The hydrogels presented prolonged larvicidal action up to 48 hours, ranging from 30 to 81.6% of the mortality index of the larvae. In this way, the system proved to be promising for prolonged larvicidal action.